Penyuluhan Kesehatan Mental Remaja Berbasis Sekolah dan Keluarga melalui Pendekatan Partisipatif di Kota Bogor - Budi Santoso; Fitri Amalia; Rizki Maulana; Nia Kurniasih; Agus Setiawan; Rendi Prakoso; Maya Lestari (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2025)
Adolescent mental health has become a critical issue in the digital era due to the increasing prevalence of depression, anxiety, and behavioral disorders. This community service program aimed to develop an integrated mental health counseling model involving schools and families in Bogor City using a participatory approach through workshops, focus group discussions, peer counseling, and six months of continuous assistance involving 250 senior high school students, 80 teachers, and 200 parents. The results showed a 78% increase in mental health literacy, a 65% reduction in stigma, and a 72% improvement in family communication, while post-program evaluation indicated that 85% of participants were able to recognize symptoms of mental health disorders and 70% actively sought professional assistance. Overall, the program successfully established a sustainable mental health support ecosystem within school and family settings, contributing to long-term improvements in adolescents’ psychological well-being.